Morphological and Physico-Chemical Characterization of Fruit of Melicoccus Bijugatus Jacq. (Bangladesh Journal of Botany, 2021)
Morphological and physico-chemical characterization of the fruit of Melicoccus bijugatus were studied. To estimate more accurate data of fruit of Melicoccus bijugatus 11 variables were valued in two different stages of maturity ripe and unripe: shelled weight, shell weight, juice weight, pulp weight, seed weight, fruit length (cm), fruit diameter (cm), thickness (mm), shell thickness (mm), seed color and seed shape. In order to obtain these analytical scales and calibrators data, the two maturity stages by tabulating and analyzing all the information collected were compared and taken into consideration the maturity index to determine the optimum point of harvest. The shell weight, juice weight, pulp weight, seed weight, fruit length, fruit diameter and shell thickness were obtained higher in the ripe fruit than the unripe fruit, when the fruits have reached 69% of maturity, recommended as optimal percentage of maturity.Bangladesh J. Bot. 50(2): 387-394, 2021 (June)